Argumentation skill through a scientific approach: Study at different school accreditations rating - Ria Afrilia; Neni Hasnunidah; Dina Maulina (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
This study aims to determine the differences in students' argumentation skills in learning biology on the subject matter of the respiratory system through a scientific approach. This research was conducted in class XII SMA in Way Kanan Regency, Lampung Province with an ex post facto design. The sampling technique used in this study was stratified random sampling with the determination of research subjects at SMAN 1 Baradatu which was accredited A, SMAN 2 Buay Bahuga was accredited B and MA Miftahul Ulum Way Tuba which was accredited C. Data collection instruments consisted of argumentation skill tests, interviews, study documentation and questionnaires. The argumentation skill data were analyzed with the help of Excel, hypothesis testing was carried out with one-way ANOVA and LSD test, interview data and learning documents were analyzed descriptively qualitatively with the Miles and Huberman model and questionnaire data were analyzed descriptively in percentage form. The results showed that there was a significant difference in argumentation skill among high school students with accreditation of A, B and C (sig. < 0.05). The average argumentation skill of students from A-accredited high schools was higher than B and C accredited high schools, but the average value of the three schools was very low. Students from A, B and C accredited high schools could make claims well, but had not been able to provide grounds, warrants and backings that are relevant to the claim. This was because students wer not used to working on argumentation questions and teachers had not optimized learning activities with a scientific approach.